Redefining Early Literacy: A STEAM Approach at AZ Zahra NU Kindergarten, Magelang - Najanuddin, Najanuddin; Setiani, Riris Eka; Listyowati, Anies (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2023)
This research investigates the implementation of a Science, Technology, Engineering, Arts, and Mathematics (STEAM)-based learning approach at AZ Zahra NU Salaman Magelang Kindergarten, aiming to enhance early childhood literacy in reading, writing, and arithmetic. Employing a qualitative, descriptive case study methodology, the study focuses on learning design, execution, and evaluation through the STEAM lens. Data were collected via observations, interviews, and documentation involving the principal, deputy principal, and classroom teachers. The learning process at Az-Zahra NU Kindergarten has transitioned from conventional drills to a STEAM approach, utilizing loose-part media and play activities tailored to each child's unique learning style. The study reveals a significant paradigm shift in early childhood education from traditional methods to a more dynamic, integrative STEAM approach. This shift promotes holistic development and simplifies educational planning, enabling educators to concentrate on adaptive, child-centric strategies. The findings highlight the successful integration of STEAM elements into the curriculum, enhancing children's engagement and creativity in learning. However, the research's limitation lies in its focus on a single institution and qualitative data, suggesting the need for broader, mixed-method studies in diverse educational settings. Future research should also include longitudinal studies to assess the long-term impacts of the STEAM approach. In conclusion, the study presents a compelling case for the widespread adoption of STEAM in early childhood education, offering a more effective and engaging method for fostering early literacy and comprehensive child development in the 21st century.